The morphology of circulus arteriosus cerebri in the porcupine (Hystrix cristata) - Aydin, A; Yilmaz, S; Dinc, G; Ozdemir, D; Karan, M (Czech Academy Agricultural Sciences, 2005)
The circulus arteriosus cerebri of the porcupine was investigated in this study. Five porcupines were used. Coloured latex was given from the left ventricles of three and from the communis carotid artery of two porcupines. The circulus arteriosus cerebri was examined after dissection was done. The basilar artery was formed by a merge of the right and left vertebral artery. The caudal communicans artery which was the caudal part of circulus arteriosus cerebri was formed by the basilar artery on crus cerebri. From caudal to cranial, the branches originating from the basilar artery and circulus arteriosus cerebri to cerebrum and cerebellum were as follows: caudal cerebelli artery, media cerebelli artery, rostral cerebelli artery, caudal choroidea artery, artery which extended to the mesencephalon, caudal cerebral artery, internal ophthalmic artery, rostral choroidea artery, media cerebral artery, rami striati and rostral cerebral artery. The rostral cerebral artery dexter and sinister joined to each other by the rostral communicans artery, forming the circulus arteriosus cerebri. It was determined that the internal carotid artery did not participate in the formation of circulus arteriosus cerebri and the arterial blood to the circulus arteriosus cerebri of porcupine is provided via the basilar artery only.
Keywords: circulus arteriosus cerebri; brain; porcupine; Hystrix cristata